Target Network Selection Algorithm based on Required Dwell Time Estimation - Jyoti Verma; Sunanda Gupta; Pratima Manhas; Vasudha Arora (IAES Indonesian Section, 2018)
In wireless communication of fourth generation the expectation to integrate a diverse heterogeneous wireless network leads to a worldwide seamless mobility. For seamless mobility in heterogenous wireless networks, selection of best target network from available network is primary goal for handovers. To achieve this goal, we devise a target network selection algorithm to enhance the user satisfaction level.The method relies on a dwell time and prediction of received signal strength. By observing the Predicted received signal strength for a specified dwell time duration, a mobile node is able to decide whether to tigger the handoff process or not. Once the handoff process is triggered. Target network is selected depending upon a cost function. The Simulated results shows that, the proposed algorithm improves the handover performance by measuring the received signal strength accurately. It also selects the optimum target network quantitatively. Therefore, results obtained through our proposed algorithm are more accurate as compared to existing handover algorithms.